An Improved Universal Suspended Hydraulic Lift - J. A. Herrick (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1879)
SOME time ago the writer needed a cheap, light, and portable hydraulic lift or crane, that would be universal in its application, and that might -be suspended from crane-arms, overhead tramways, beams, etc., and serve all the uses of ordinary hydraulic cranes. This was accomplished by the use of a closed cylinder of wrought-iron hydraulic pipe, provided at its top with the ordinary gland and stuffing-box, through the centre of which passed another similar pipe of slightly smaller diameter, forming in effect the ordinary plunger of the regular hydraulic crane. Over the top of this centre pipe or plunger or piston a disk of iron is placed with two arms projecting several inches from the rim, as may be required. Through these arms long iron rods pass, one on each. side, and are fastened in place by nuts screwed to a bearing immediately above and below the disk. These rods also pass through the enlarged head of the lift down through a casting which closes the bottom of the cylinder, which, at the same time, gives them a bearing, and they terminate at a point below the casting equal to the height of the lift of the crane. The rods at this point pass through a disk similar to the top disk and are similarly secured in place. A common hook arranged with a swivel passes through the centre of the disk, and on this hook the load is suspended. For a stationary hanging crane the apparatus is suspended by two rods passing through the head of the lift in similar manner to the two already described, at right angles to the first, and of sufficient length to let the first set play between them and rise to the full height which the plunger will allow. The second set of rods terminates in an iron disk similar to the one at the bottom of the first set, and a hook through this in turn suspends the entire apparatus. In order to adapt the lift to an overhead tramway, single or double, in place of the suspending rods, a projection or offset is arranged on each side of the head of the lift and a journal cast in, allowing the lift to be suspended on pivots arranged as follows